Study of the profile of bioactive compounds of the early Isabel grape cultivar (Vitis labrusca l) cultiated in the brazilian savanna (Research, Society and Development, 2020)
The objective of the present study was to evaluate the behavior of the bioactive compounds during the physiological development of the early Isabel grape cultivar (Vitis labrusca L), cultivated in the Brazilian savanna, with a view to future applications. This is a quantitative study carried out in the field and in the laboratory.The physical and chemical characterization was performed total phenolic compounds, antioxidant activity and the profile of the phenolic compounds by HPLC. The physical and chemical transformations of the berries were much more intense as from 60 DAA. The seeds presented high antioxidant potential in two analyzed methods. Three were phenolic compounds identified, chlorogenic acid being present in the berries, skins and pulps, catechin being present in the largest amounts, followed by epicatechin, present in the seeds. Such knowledge is important for future extractions and applications in foods and cosmetics.